What is Copyright? Communicating specialized knowledge on CBBC - Cacchiani, Silvia (Jan Kochanowski University Press, 2022)
The paper provides a qualitative investigation into the many ways in which exposition mediates exclusive knowledge about copyright to children in Key Stage 3 on the Bitesize and Newsround pages of the British Children’s BBC online platform. The analysis compares objective exposition in the copyright article of OUP’s A Dictionary of Law, primarily intended for inclusion and knowledge transfer to late youth and adults, with the Bitesize sister directories on Copyright and intellectual property, and a Newsround story about EU copyright law. Data suggests that the Bitesize pages address excellent readers using specialist terminology; they pursue brevity, precision, and conciseness. While still comprising expository passages for explanatory purposes, Newsround adopts interlocutive strategies and provides verbal and visual stimuli – including clever language play within memes – that are clearly intended to engage with users, arouse their curiosity, and promote identification with the represented participants and actions.